Variáveis relacionadas com a distribuição regional, dominância e estruturação de comunidades de peixes em riachos. - Oliveira, Fagner Junior Machado de (2020)
Different ecological processes (e.g., rescue effect, environmental filtering, limiting similarity and dispersal) shape the structure of ecological communities. These processes, which are related to the theories of metapopulation and metacommunities, guided this study. For this purpose, data from fish communities in streams in the Upper Araguaia river basin (Mato Grosso and the Goiás States, Brazil) were used. It was observed that the regional distribution of fish species was modelled according to niche attributes (position and breadth), body size, trophic position, and swimming capacity. The results indicated that average abundance, niche position and niche amplitude predict the regional distribution of the species. Taken together, these results suggest the importance of metapopulation dynamics and niche-based processes explaining the regional distribution of species in the studied system. At another time, it was tested whether the abundance of subordinate species (i.e., any species that are not dominant in a local community) was correlated with the functional distance between dominant and subordinate species. In the results, a negative relationship between these quantities and that the subordinate species had larger body sizes compared to the dominant species in the local communities. These results also suggest that species filtering is more important than the interspecific competition to explain the patterns of species abundance distribution. In this study, was analyzed the relative importance of local environmental, landscape and spatial variables in structuring fish communities in streams of “veredas” (small wetlands in the Cerrado). The local environmental variables, after controlling the effect of space, were clearly more important than those obtained at the landscape scale. In view of the observations, it is concluded that the use of landscape data, in studies seeking environmental correlates of local community structure, should not occur at the expense of obtaining local variables (mainly those related to the habitat structure). The results of the three investigations in this study shown the predominant role of local environmental filters in the structuring of the fish communities analyzed. Species with high niche amplitude tend to have wide regional distributions and small-bodied ones tend to be locally dominant.